Odpowiedzi

2010-01-04T16:00:35+01:00
5(x + 7)² - 5x² = 105
(5x+35)² - 5x² = 105
5x² + 2*5x*35+14 - 5x²=105
5x² +350x- 5x²=105
350x=105/350
x=0,3

(x + 5)² - (x + 3)(x - 3) + 56 = -30
x²+2*x*5+5²+25-x²-3³+56=-30
x²+10x+25-x²-9+56=-30
10x=-30-56+9-25
10x=-102/10
x=-10,2
2010-01-04T16:21:06+01:00
5(x + 7)² - 5x² = 105
5(x2 +49 +14x) - 5x2= 105
5x2 + 245 +70x -5x2= 105
70x=-140
x= -2




(x + 5)² - (x + 3)(x - 3) + 56 = -30
(x2+25+10x) - (x2-9) +56= -30
x2+25+10x -x2 +9 +56= -30
10x= -30 - 90
x=12



(x - 3)² > (x - 1)(x + 2) +4
(x2 +9-6x) > x2 - 2x -1+2 +4
-6x+2x> 5-9
-4x>-4
x<1



(x - 4)(x + 4) - x² < 2(x - 3)
(x2 -16)-x2<2x-6
-16<2x-6
-10<2x
x>-5



7(6x - 1) -2(x + 3)² ≤ 3(x +2)² - 5(x - 1)²
(42x-7)-2(x2 +9+6x)≤ 3(x2+4+4x)-5(x2+1-2x)
42x-7 -2x2-18-12x≤ 3x2+12+12x-5x2-5+10x
42x -12x -22x≤ 12-5 +7+18
8x≤ 32
x≤4